Neutrophil/Lymphocyte Ratio as an Inflammatory Predictor of Dry Eye Disease: A Case-Control Study - Meng YF; Pu Q; Ma Q; Zhu W; Li XY (Dove Medical Press, 2021)
Yi-Fang Meng,1,2,* Qi Pu,1,* Qian Ma,1 Wei Zhu,2 Xin-Yu Li1 1Department of Ophthalmology, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, People’s Republic of China; 2Department of Ophthalmology, Changshu No. 2 People’s Hospital, Changshu, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xin-Yu LiDepartment of Ophthalmology, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, 1095 Jiefang Avenue, Wuhan, Hubei, 430030, People’s Republic of ChinaTel/Fax +86-027-83663456Email xinyu@tjh.tjmu.edu.cnWei ZhuDepartment of Ophthalmology, Changshu No. 2 People’s Hospital, Changshu, Jiangsu, People’s Republic of ChinaEmail shzhuwei0722@163.comBackground: The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) have been used as indicators of inflammation, however, their roles in dry eye disease (DED) patients require advanced studyMaterials and Methods: A total of 104 DED cases and 97 healthy controls from January 2020 to May 2020 were enrolled in this study. The dry eye related clinical variables, including Schirmer I test, tear break-up time (TBUT), corneal fluorescein staining (CFS) and Ocular Surface Disease Index (OSDI), were detected in all the participants. Besides, the NLR and PLR pattern in DED cases were detected and their potential value as inflammatory predictors of DED were evaluated. In advanced analyses, the correlation between NLR and DED severity was examined.Results: The NLR and PLR were 2.59 ± 1.25 and 117.48 ± 54.68 in the DED group, respectively, while they were 2.20 ± 1.24 and 115.48 ± 54.33 in the control group, respectively. The NLR was higher in the DED group (p = 0.027), however, PLR was not significantly different compared with the control group (p = 0.951). In advanced analyses, it was found that more severe TBUT, CFS, and OSDI scores were detected in the high NLR group (NLR ≥ 2.145, p = 0.003, 0.013, and 0.017, respectively) compared with the low NLR group (NLR < 2.145).Conclusion: The NLR value, but not PLR, of DED patients was higher than that of healthy controls. The NLR could be used as an inflammatory predictor to estimate the severity of DED.Keywords: dry eye disease, neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, case-control study, risk factor